An NHC-catalyzed [3+2] cyclization of β-disubstituted enals with benzoyl cyanides. Issue 70 (4th August 2022) - Liu, Wangsheng; Zhang, Linrui; Liao, Xiaoyun; Chen, Jiean; Huang, Yong
Abstract : The NHC-catalyzed asymmetric [3+2] cyclization of benzoyl cyanides to homoenolate generated in situ from enals was reported. Abstract : The NHC-catalyzed asymmetric [3+2] cyclization of benzoyl cyanides to homoenolate generated in situ from enals was reported. This methodology leads to the efficient construction of a series of chiral cyclic compounds bearing vicinal quaternary stereocenters under mild reaction conditions. Additionally, the representative large-scale and derivatization reactions of the chiral cyclic products reveal the potential synthetic utility of this protocol.